Digital Transformation in Traditional Sectors: The Role of Perceived Security and Enjoyment in Fintech Syariah Adoption among Batik MSMEs - Muhammad Sulthoni; Haryanto Kanthi Widodo; Wahid Wachyu Adi Winarto; Hendri Hermawan Adinugraha; Akbar Sarif (TIJAB (The International Journal of Applied Business), 2026)
Background: This study aims to investigate the determinants that influence the sustainability intention of using Sharia Fintech among Batik MSME actors. Objective: Expanding the integrated framework of the Expectation-Confirmation Model (ECM) and the Technology Acceptance Model (TAM) by incorporating perceived security and pleasure as additional variables. Method: This study employed a quantitative approach using a snowball sampling technique. A total of 143 respondents, consisting of Batik entrepreneurs who utilize Islamic fintech, were collected and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among constructs. Result: The findings of the study show that the proposed integrative model has a very strong capacity to explain user behavior. Attitudes, satisfaction, and social influence are proven to be the main drivers that determine the intention of artisans to continue participating in the digital financial ecosystem. In particular, the confirmation of expectations emerged as the most dominant factor in shaping the perception of usability and user satisfaction. Conclusion: Although functional usability plays an important role in shaping attitudes, its impact on immediate satisfaction was found to be insignificant, suggesting that in the cultural heritage industry, emotional value and a sense of security take precedence over mere technical efficiency. This research makes an original contribution by validating the importance of affective and security aspects in accelerating digital transformation in the batik MSME sector. In practical terms, these results suggest that Sharia Fintech service providers focus on increasing transparency and features that improve users' psychological comfort to ensure long-term user loyalty. Keywords: Sharia Fintech, Batik MSMEs; Sustainability Intentions; Expectation Confirmation Model; Digital Transformation.